The Implementation Of Demonstration Method In Enhancing Arabic Language Learning Outcomes Among MI Aisyiyah Students - Rahmat, Nur; Wajdi, Muh Barid NIzarudin (IERA, Islamic Education and Research Academy, 2023)
The implementation of the demonstration method aims to improve Arabic language learning outcomes. This study also seeks to identify the supporting and inhibiting factors associated with this method. A qualitative approach was employed, with the demonstration method specifically applied to the topic of "arriyadoh" (sports). The use of the demonstration method in Arabic language instruction is expected to facilitate students in retaining vocabulary (mufrodat) over a long period, thereby addressing the needs for vocabulary mastery and significantly impacting students' learning outcomes. The results indicate that the application of the demonstration method has led to an improvement in student learning outcomes. The demonstration method in Arabic language teaching was effectively implemented, as evidenced by the well-planned and executed teaching process, resulting in a clearer and more concrete learning experience